Exodoncia, regeneración ósea, implantes, reporte de un caso - Jorge Alberto Arismendi-Echavarria (Universidad de Antioquia, 1999)
There are many different indications for a tooth extraction. The decision is generally made by general dentists. The way the extraction is made will define the aesthetic and functional results of the final restoration. This case report shows how the first molar extraction and its posterior implant restoration was performed (two RESTORE9 screw-type implants). The origin of guided bone regeneration is discussed. Today, the dentists may choose either immediate or delayed implant placement according to the bone condition in the extraction site. Tha last choice requires guided bone regeneration to produce a more predictable result. This information would help general dentists to accomplish the extraction site in a conservative way, preventing bone ridge atrophy to obtain better aesthetic and functional final restorations